FORENSIC DENTISTRY IN ACCORDANCE WITH CURRENT LITERATURE - Türkcan, Mehmet Buğra; Baybars, Sümeyye Coşgun (Mesut TUZLALI, 2024)
Forensic dentistry; It is a branch of dentistry that supports justice in terms of identification and evidence determination, age and gender determination, and medical legal obligations of dentists by evaluating dental findings in forensic events. The fact that the teeth and oral cavity structures are unique to the individual and the hard structural properties of the teeth are mechanical, chemical, etc. resistance to stimuli and time has increased the importance of these data. In forensic dentistry, the methods used in identification and information gathering techniques have undergone significant changes over the years. By incorporating innovations on previously used methods, dental radiographs (Radiovisiograph, etc.) taken using comparative or reconstructive methods, bite mark analyzes made by looking at the size of the dental arch, shape of the jaw arch and tooth alignment, in cases where known identification methods fail due to trauma and deterioration. Methods such as DNA analysis using oral tissues, age determination using dental tissues (mineralization, hard tissue calcification, apex condition) and gender determination by looking at the characteristic features of the jaw and teeth have also been developed. In addition to these methods, rugoscopy, lip print analysis, digital reconstruction, use of prosthetic ID (barcodes, microchips) are innovations that have joined the forensic dentistry. Artificial intelligence-based deep learning methods, which have been developing day by day, have started to be used in the solution of many problems in forensic dentistry today. The purpose of these developing methods is to automate the work done by people today, and to reduce the margin of error in the decision phase as it includes features that cannot be distinguished with the human eye on the data. Physicians should know dental identification techniques and be aware that dental and oral structures will be used in forensic dentistry. Therefore, the dental records of the patients should be preserved, archived and accessible in accordance with international standards, and a database should be prepared to ensure that identification is fast and easy. The aim of this review is to evaluate the newly developed methods of digital tooth reconstruction, prosthesis ID and artificial intelligence use in the light of current literature, as well as the old methods used in forensic dentistry.

Adli diş hekimliği; adli olaylarda dental bulguları değerlendirerek kimlik ve delil tespiti, yaş ve cinsiyet tayini, diş hekimlerinin tıbbi açıdan hukuki yükümlülükleri konusunda adalete destek olan diş hekimliğinin bir dalıdır. Dişler ve oral kavite yapılarının bireye özgün olması ve dişlerin sert yapısal özelliklerinin mekanik, kimyasal vb. uyaranlara ve zamana karşı dayanıklılığı bu verilerin önemini arttırmıştır. Adli diş hekimliğinde, kimliklendirmede kullanılan yöntemler ve bilgi toplama teknikleri yıllar içinde kayda değer değişimler geçirmiştir. Önceden kullanılan yöntemler üzerine yenilikler katılarak, karşılaştırmalı veya rekonstrüktif yöntem kullanılarak alınan dental radyograflar (Radiovisiograf vb.), diş arkının boyutu, çene kavsinin şekli ve diş dizilim şekline bakılarak yapılan ısırık izi analizleri, travma ve bozulmalardan dolayı bilinen kimlik tayin etme metotlarının başarısız olduğu durumlarda oral dokular kullanılarak yapılan DNA analizleri, dental dokuların (mineralizasyon, sert doku kalsifikasyonu, apeks durumu) kullanılarak yaşın belirlenmesi ayrıca, çene ve dişlerin karakteristik özelliklerine bakılarak yapılan cinsiyet belirleme gibi yöntemler de geliştirilmiştir. Bu yöntemlere ek olarak, rugoskopi, dudak izi analizi, dijital rekonstrüksiyon, protez ID (barkodlar, mikroçipler) kullanımı adli diş hekimliğine katılmış yeniliklerdir. Son zamanlarda günden güne gelişen yapay zeka temelli derin öğrenme yöntemleri, günümüzde adli diş hekimliğinde bir çok problemin çözümünde kullanılmaya başlanmıştır. Bu gelişen yöntemlerin amacı günümüzde insanlar tarafından yapılan işleri otomatikleştirmek, veri üzerinde insan gözü ile ayırt edilemeyecek özellikleri de araştırmaya dâhil ettiği için karar aşamasında hata payını azaltmaktadır. Hekimler dental kimliklendirme tekniklerini bilmeli dental ve oral yapıların adli diş hekimliğinde kullanılacağının bilincinde olmalıdır. Bu yüzden hastaların dental kayıtları uluslararası standartların belirttiği şekilde muhafaza edilmeli, arşivlenmeli, ulaşılabilir olmalı, veri bankası hazırlanarak kimlik tespitinin hızlı ve kolay olması sağlanmalıdır. Bu derlemenin amacı, adli diş hekimliğinde kullanılmakta olan eski metotların yanında yeni geliştirilen dijital diş rekonstrüksiyonu, protez ID ve yapay zeka kullanımı yöntemlerinin güncel literatür eşliğinde değerlendirilmesi amaçlanmaktadır.
GÜNCEL LİTERATÜR EŞLİĞİNDE ADLİ DİŞ HEKİMLİĞİ
Keywords: Dentistry; Diş Hekimliği